Exploring the immediate effects of aerobic exercise on nocturnal blood pressure dip in medication-controlled hypertensive individuals: a randomised controlled trial - Lopez, Ericka Arrazola; Cavalari, João Vagner; Grandolfi, Kamila; Christofaro, Diego Giulliano Destro [UNESP]; Aguiar, Andreo Fernando; Borghi, Sergio Marques; Casonatto, Juliano (Taylor & Francis, 2025)
Background: Nocturnal blood pressure dipping is crucial for cardiovascular health, but the effect of exercise on this phenomenon is not well understood. This study aims to investigate how a single session of aerobic exercise impacts nocturnal blood pressure dipping in individuals with hypertension who are on medication. Methods: Twenty hypertensive adults (67 ± 16 years) participated in a randomised, parallel-group clinical trial. They were randomly assigned to either an exercise or control group. Resting blood pressure was measured after a 20-minute period of comfortable seating in a calm environment. The exercise group performed 40 min of treadmill running/walking at an intensity of 60-70% of their reserve heart rate. The control group remained seated for an equivalent period with reading allowed. Ambulatory blood pressure monitoring was used to measure blood pressure over 24 h. Nocturnal dip was calculated by comparing the mean wakefulness and sleep blood pressure values. Results: No significant differences were observed between the exercise and control groups in systolic and diastolic blood pressure values at rest, during wakefulness, sleep, or over 24 h. The absolute nocturnal dip also showed no significant differences between the groups for systolic blood pressure (MD = 3.00 [95% CI: −4.77 to 10.77] p = 0.428) or diastolic blood pressure (MD = 4.60 [95% CI: −2.81 to 12.00] p = 0.208). Similarly, the relative nocturnal dip (percentage) did not differ significantly for systolic blood pressure (MD = 0.029 [95% CI: −0.039 to 0.837] p = 0.465) or diastolic blood pressure (MD = 0.047 [95% CI: −0.036 to 0.132] p = 0.250). Conclusions: A single session of aerobic exercise does not impact the nocturnal dip in systolic and diastolic blood pressure in medication-controlled hypertensive individuals.
Keywords: ambulatory blood pressure monitoring; hypertension; Post-exercise hypotension; sleep